PENGGUNAAN MEDIA AUDIO UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK DONGENG ANAK PADA SISWA KELAS IV SEKOLAH DASAR - Widyaningrum, Heny Kusuma (Premiere Educandum, 2015)
In elementary school, attentiveness is an important language skill. On the other hand, the fact shows that the lesson of attentiveness still low ang students interest is poor. Thus, the use of proper media can be considered in order to make lessons goal of attentive skill is approachable. Based on the above reason, this research purposes to improve attentive skill in myth in fourth grade students in SDN Sambirejo 1 Madiun by using audio media, that is myth recording. This research uses Classroom Action Research consist of two cycles. The result research shows the improvement on dispute the characters and the scene. Lessons process is in these aspects: attention, seriousness, and activeness are improve up to 11,8%. Result of improvement of attentive skill in myth in aspect characters and scene in the first cycle and second cycle are improve in average of 17,3% and7,4%. Key words: audio nedia, attentive skill, myth